2013
DOI: 10.1007/s00266-012-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Breast Reduction on the Postural Control of Women with Breast Hypertrophy

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Symmetry, natural shape, and proper size are biologically and esthetically important. An extremely large breast size may lead to difficulties in daily life and studies have demonstrated that physical weight and psychological factors may cause an altered skeletal posture (1)(2)(3). Moreover, many studies have reported that having both breasts is important in maintaining a center of gravity and stable posture (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Symmetry, natural shape, and proper size are biologically and esthetically important. An extremely large breast size may lead to difficulties in daily life and studies have demonstrated that physical weight and psychological factors may cause an altered skeletal posture (1)(2)(3). Moreover, many studies have reported that having both breasts is important in maintaining a center of gravity and stable posture (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Sahin et al 19 used 3D gait analysis on 10 patients to demonstrate a statistically significant improvement in maximum anterior pelvic tilt (41% reduction), average maximum spine anterior flexion (30% improvement), and an improved body posture when walking after breast reduction surgery. In the study by Barbosa et al, 23 it was demonstrated that postoperative patients had a smaller center-of-displacement area and improved postural control. Tenna et al 24 demonstrated, by means of static stabilometry, that postoperative reduction mammaplasty patients have objectively improved posture at the 6-month postoperative mark ( P = 0.032).…”
Section: Resultsmentioning
confidence: 96%
“…In all studies that applied a component of pain evaluation, a significant improvement in pain postoperatively was demonstrated. 17,20,23,25,26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, could be inferred that breast size influences the postural biomechanics. When assessing static balance in women with breast reduction, there is a decline in both, area and velocity displacement [21]. Barbosa et al [22] showed an increase in the area and velocity displacement of the pressure center of women with breast hypertrophy.…”
Section: Discussionmentioning
confidence: 99%